Post-systolic shortening index by echocardiography evaluation of dyssynchrony in the non-dilated and hypertrophied left ventricle. (3rd October 2022) - Wang, T K M; Saijo, Y; Chan, N; Sperry, B; Phelan, D; Desai, M Y; Griffin, B P; Grimm, R A; Popovic, Z B
Abstract: Background: Post-systolic shortening index (PSI) is defined as myocardial shortening that occurs after aortic valve closure, and is an emerging measure of regional LV contractile dysfunction. PSI measurement variability amongst software vendor and its relationship with mechanical dyssynchrony and mechanical dispersion index (MDI) remains unknown. We evaluated PSI by speckle-tracking echocardiography from several vendors in patients with increased left ventricular wall thickness, and associations with MDI. Methods: This is a prospective cross-sectional study of 70 patients (36 hypertrophic cardiomyopathy [HCM], 18 cardiac amyloidosis and 16 healthy controls) undergoing clinically indicated echocardiography. PSI was measured using QLAB/aCMQ (Philips), QLAB/LV auto-trace (Philips), EchoPAC (GE), Velocity Vector Imaging (Siemens), and EchoInsight (EPSILON) software packages, and calculated as 100% × (post systolic strain − end-systole strain)/post systolic strain. Results: There was a significant difference in mean PSI among controls 2.1±0.6%, HCM 6.1±2.6% and cardiac amyloidosis 6.8±2.7% (p<0.001). Variations between software vendors were significant in patients with pathologic increases in LV wall thickness (for HCM p=0.03, for amyloidosis p=0.008), but not in controls (p=0.11), as seen in Figure 1. Furthermore, there were moderate correlations between PSI and both MDI (r=0.77) and left ventricular global longitudinal strain (r=0.69), as seen in Figure 2. Conclusion: PSI was greater in HCM and cardiac amyloidosis patients than controls, and a valuable tool for dyssynchrony evaluation, with moderate correlations to MDI and strain. However, there were significant variations in PSI measurements by software vendor especially in patients with pathological increase in LV wall thickness, suggesting that separate vendor-specific thresholds for abnormal PSI are required. Funding Acknowledgement: Type of funding sources: None.